Pseudogap and Local Pairs in High-Tc Superconductors - Solovjov, A.L.; Tkachenko, M.A. (Металлофизика и новейшие технологии, 2013)
The temperature (T) dependence of pseudogap (PG) Δ*(T) is calculated for Bi2201 within the local pair (LP) model [1, 2]. The model is based on analysis of the excess conductivity derived from resistivity experiments in hightemperature superconductors (HTSs) and supposes the local pairs, which are formed in HTSs at T well above Tc, to generate a pseudogap. To confirm the conclusion, Δ*(T) is compared with the temperature dependence of the loss of the spectral weight W(EF)(T) measured by ARPES for the same Bi2201 sample [3]. A good agreement between Δ*(T) and W(EF)(T) is found, confirming the local pairs to be one of the most likely cause for the PG formation.